The Current State of Nuclear Nephrology in Modern Medicine - Miladinova, Daniela; Makazlieva, Tanja; Peshevska, Aleksandra; Rambabova Bushljetic, Irena; Poposka, Daniela; Majstorov, Venjamin; Spasovski, Goce (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2023)
Glomerular filtration rate (GFR) is the most reliable parameter of renal function. Regarding the complexity of the gold standard inulin clearance, different estimating equations have been developed with CKD-EPI creatinine equation recommended as the most reliable one. In some clinical situations where creatinine based equations might not be valid, alternative methods are needed. Nuclear medicine methods for measuring GFR with 51Cr EDTA and 99mTc DTPA have been widely used for decades. There are different methodologies for the measurement of kidney function with radiopharmaceuticals: urinary clearance, plasma clearance, multiple plasma sampling, slope intercept, single sample plasma equation, slope only, and the gamma camera-based method. Greater precision of measuring GFR is needed in certain clinical situations. The most common are diagnosis and follow up of chronic kidney disease and definition of the beginning of replacement therapy. The assessment of renal function is also important for potential kidney donors. In recent years, with the introduction of new chemotherapeutic drugs and targeted therapy, oncologic patients treated with nephrotoxic drugs have become more commonly referred for measuring GFR. The monitoring of renal function is important during treatment in order to detect the transformation from reversible acute kidney injury to irreversible chronic kidney disease as well as in the cases of renal insufficiency reduce the dosage and prevent accumulation of the drug and avoid dosage related toxic effects. Assessment of kidney function using measured mGFR will be an important milestone in the creation of more accurate and expanding personalized medicine principle in current onconephrology practice.
Keywords: glomerular filtration rate; nuclear medicine methods; nephrotoxicity; onconephrology